Innovative technologies in the water and waste industries for the 21st century : proceedings - Frederick-van Genderen, Gelia (The Water Authority Grand CaymanKY, 2001)
Covers topics ranging from innovative approaches to wastewater treatment; advances in desalination technology; use of GIS in the water and wastewater sector; challenges in human resource management; implementing automated meter reading; wellfield design; reuse of wastewater; rehabilitation technologies for wastewater collection systems; public health and environmental impacts and mitigation of the water and wastewater industry; quality control; and, advances in solid waste management.